Childhood overweight and obesity and timing of puberty in boys and girls: cohort and sibling-matched analyses. (5th May 2020) - Brix, Nis; Ernst, Andreas; Lauridsen, Lea Lykke Braskhøj; Parner, Erik Thorlund; Arah, Onyebuchi A; Olsen, Jørn; Henriksen, Tine Brink; Ramlau-Hansen, Cecilia Høst
Abstract: Background: Early puberty is a risk indicator for adult diseases. Identification of modifiable causes of earlier puberty is, therefore, warranted. We estimate the association between childhood body mass index (BMI) and pubertal timing in a cohort study and in a sibling-matched study to adjust for unobserved time-stable confounders shared within families. Methods: For the cohort study, 11 046 of 22 439 (49%) invited children, born 2000–203, from the Danish National Birth Cohort (DNBC) had information on childhood BMI at 7 years and self-reported, half-yearly puberty information from 11 years on Tanner stages, menarche, voice break, first ejaculation, acne, and axillary hair. For the sibling-matched study, 1700 brothers and sisters were included among 86 820 live-born singletons from the DNBC. Results: Childhood overweight (85th ≤ BMI < 95th percentile) and obesity (BMI ≥ 95th percentile) were associated with earlier age attaining the pubertal milestones in a dose-dependent manner in boys and girls. When modelling all pubertal milestones simultaneously, the pubertal milestones were attained earlier in: overweight boys: −3.1 [95% confidence interval (CI): −4.5, −1.7] months, overweight girls: −5.5 (95% CI: −7.1, −3.9) months, obese boys: −3.5 (95% CI: −5.1, −2.0) months, obese girls: −5.2 (95% CI: −7.1, −3.4) months compared with normal weight (BMI < 85th percentile) children. In the sibling-matched study, higher BMI was associated with earlier age at attaining most pubertal milestones in girls, but only a tendency toward earlier pubertal timing was observed in boys. Conclusions: Childhood overweight and obesity were associated with earlier pubertal timing even after adjustment for unobserved time-stable confounders shared within families.